Labor Market Effects of Sports and Exercise: Evidence from Canadian Panel Data - Michael Lechner; Nazmi Sari (Institute for the Study of Labor (IZA), 2014)
Based on the Canadian National Population Health Survey we estimate the effects of individual sports and exercise on individual labor market outcomes. The data covers the period from 1994 to 2008. It is longitudinal and rich in life-style, health, and physical activity information. Exploiting these features of the data allows for a credible identification of the effects as well as for estimating dose-response relationships. Generally, we confirm previous findings of positive long-run income effects. However, an activity level above the current recommendation of the WHO for minimum physical activity is required to reap in the long-run benefits.
Keywords: I12; I18; J24; L83; C21; 330; physical activity; Canadian National Population Health Survey; individual sports participation; human capital; labor market; matching estimation